2017
DOI: 10.1371/journal.pone.0176758
|View full text |Cite
|
Sign up to set email alerts
|

Egg production patterns of two invertebrate species in rocky subtidal areas under different fishing regimes along the coast of central Chile

Abstract: Fishing is a major source of human impact, reducing density and size of a wide range of exploited species in comparison to areas exhibiting strong regulations (no-take and partially protected areas, including Territorial Use Rights for Fisheries, TURFs). Since size and density might have important consequences on reproduction, and therefore natural re-seeding, we monitored adult size, density and potential fecundity of the keyhole limpet (Fissurella latimarginata) and the red sea urchin (Loxechinus albus) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Habitat distribution was obtained by characterizing the habitat type (rock vs. sand) in each of the latitudinal cells using high resolution satellite photography (Fig.1, left panel) for the intertidal zone and projecting this onto a uniform shallow subtidal band down to a depth of 200 m. Combined, these two data sources describe the proportion of rocky coast covered by MA in each cell. The remaining fraction of rocky coast in each cell was assumed to be open access (hereafter OA; see Blanco et al, 2017, for details).…”
Section: Model Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitat distribution was obtained by characterizing the habitat type (rock vs. sand) in each of the latitudinal cells using high resolution satellite photography (Fig.1, left panel) for the intertidal zone and projecting this onto a uniform shallow subtidal band down to a depth of 200 m. Combined, these two data sources describe the proportion of rocky coast covered by MA in each cell. The remaining fraction of rocky coast in each cell was assumed to be open access (hereafter OA; see Blanco et al, 2017, for details).…”
Section: Model Domainmentioning
confidence: 99%
“…Based on these studies (see Blanco et al, 2017Blanco et al, , 2019, for details), we estimated that net larval production in MAs was 17% less than in NT areas, which was the baseline (Table 1). Scale factors to estimate L in open access areas were calculated for each species from field work and laboratory experiments (see Blanco et al, 2017). Afterwards, L per cell was estimated based on potential fecundity per unit of rocky area for the different fishing regimes (see Blanco et al 2017 and eqs.…”
Section: Biological Datamentioning
confidence: 99%
“…In open access areas, it has been estimated that 22 million larvae are released every 90 m 2 . On the other hand, in TURFs, a 20‐fold increase in release of larvae is estimated (Blanco, Ospina‐Alvarez, Gonzalez, & Fernandez, ). Other invertebrate benthic species of commercial importance (the keyhole limpet Fissurella latimarginata and the red sea urchin Loxechinus albus ) also have higher potential fecundity within TURFs than in open access areas as they reach larger size and consequently produce larger gonads (Fernandez, Blanco, Ruano‐Chamorro, & Subida, ).…”
Section: Resultsmentioning
confidence: 99%
“…In open access areas, it has been estimated that 22 million larvae are released every 90 m 2 . On the other hand, in TURFs, a 20-fold increase in release of larvae is estimated (Blanco, Ospina-Alvarez, Gonzalez, & Fernandez, 2017).…”
Section: Turfs and Regulating Services: Larvae Production And Climatementioning
confidence: 98%
“…TURFs are expected to secure fisheries harvests within their boundaries and provide incentives for sustainable use of surrounding fishing grounds (Christy 1982). Recent studies in the Chilean system of TURFs have shown higher potential egg production of two benthic species (the limpet Fissurella latimarginata and the red sea urchin Loxechinus albus) within TURFs than under an open access scenario (67% and 52% higher, respectively) (Blanco et al 2017), suggesting the potential to enhance fishing opportunities both inside and outside TURFs. Negative impacts of TURFs and other entry-restriction management and conservation tools beyond their limits are less well known.…”
Section: Potential Positive or Negative Interactions Between Maintainmentioning
confidence: 99%